PELAKSANAAN PENGAWASAN IZIN MENDIRIKAN BANGUNAN OLEH DINAS CIPTA KARYA DAN TATA RUANG DI KABUPATEN SIAK - Elsi Febri Mingsi; Ernawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aimed to determine the Implementation Monitoring Department of Human Settlement and Spatial Planning to the problems that occur in Siak for example, are buildings that do not have a permit, there are buildings that violate Line Border road, kemuidan absence of strict sanctions from the relevant office to public who do not have the IMB. With the formulation of research problems that How Execution Monitoring Office of Human Settlements and Spatial Siak district of the building permit and the factors that hinder the implementation of building permit supervision by the Office of Copyright works and Spatial Planning. Picture of the phenomenon or social phenomena studied by describing the independent variables systematically and accurately. Methods of data collection was done by interview, observation, and study kepustakaan.Jenis this research is descriptive in which researchers provide descriptions and.The results showed that the implementation of the Control of Building Permit by the Department of Human Settlements and Spatial Siak not maximized. This is due to lack of socialization, lack of personnel and vehicles then also lack partisipsi community towards the maintenance of the IMB. In order to achieve optimal supervision needs to be done a thorough socialization into areas so that no more buildings are not air-IMB.Keyword : supervision and building permits